Evaluasi Implementasi Binus Online pada Proses Pembelajaran Studi Kasus: Program Studi Sistem Informasi - G. G. Faniru Pakuning Desak; Nyoman Ayu Gita Gayatri (ULTIMA InfoSys, 2016)
The aim of evaluating BINUS Online inInformation System course at BINUS University is to know the factors and indicators that affect the course of study, and to determine the suitable evaluation model from past implementation. The questionnaires were distributed to all BINUS Online Learning undergraduate students of Information Systems who had used the LMS BINUS Online. The result of the survey is then evaluated using SPSS software to determine the reliability, validity, factor analysis, and regression. There are five new factors found from the survey result namely, Technology Friendly, KMS Friendly, Information Update, People Sharing and Development Learning. Keywords: Evaluation, Factor Analysis, Regression